ALEPH: a network‐oriented approach for the generation of fragment‐based libraries and for structure interpretation. Issue 3 (5th March 2020) - Medina, Ana; Triviño, Josep; Borges, Rafael J.; Millán, Claudia; Usón, Isabel; Sammito, Massimo D.
Abstract : ALEPH characterizes the main‐chain geometry of small, noncontinuous fragments to flexibly annotate secondary structure, decompose folds, extract libraries and superpose fragments. Secondary and tertiary structure are described through networks of characteristic vectors, which are defined between the centroids of the C α and carbonyl O atoms in a peptide. Abstract : The analysis of large structural databases reveals general features and relationships among proteins, providing useful insight. A different approach is required to characterize ubiquitous secondary‐structure elements, where flexibility is essential in order to capture small local differences. The ALEPH software is optimized for the analysis and the extraction of small protein folds by relying on their geometry rather than on their sequence. The annotation of the structural variability of a given fold provides valuable information for fragment‐based molecular‐replacement methods, in which testing alternative model hypotheses can succeed in solving difficult structures when no homology models are available or are successful. ARCIMBOLDO_BORGES combines the use of composite secondary‐structure elements as a search model with density modification and tracing to reveal the rest of the structure when both steps are successful. This phasing method relies on general fold libraries describing variations around a given pattern of β‐sheets and helices extracted using ALEPH . The program introduces characteristic vectors defined from the main‐chain atoms as a way to describe the geometrical properties of the structure. ALEPH encodes structural properties in a graph network, the exploration of which allows secondary‐structure annotation, decomposition of a structure into small compact folds, generation of libraries of models representing a variation of a given fold and finally superposition of these folds onto a target structure. These functions are available through a graphical interface designed to interactively show the results of structure manipulation, annotation, fold decomposition, clustering and library generation. ALEPH can produce pictures of the graphs, structures and folds for publication purposes.